Analysis of Factors Affecting Permeability of Cement-bentonite Mud Impervious Wall. Issue 1 (March 2020) - Su, Shengxi; Ding, Jihui; Zhang, Tianyu; You, Kaikai; Gan, Yu; Yan, Meng; Feng, Zhongmin
Abstract: The permeability coefficient of the cement-bentonite mud anti-seepage wall is measured by triaxial permeability test (100kPa confining pressure 80kPa osmotic pressure), variable head permeability test and one-dimensional consolidation test (100kPa consolidation pressure). Under the conditions of different indoor mixing proportions, the effects of water-cement ratio, water bentonite ratio, curing age, and a small amount of silty clay soil on the permeability of the impervious wall were studied. The test results show that: (1) The average value of the ratio of the permeability coefficient of the variable head test and the triaxial permeability test is 16.75 and 16.73 at the age of 28d and 60d, respectively, and the coefficient of variation is 0.27 and 0.35, respectively; The average value of the ratio of the permeability coefficient of the one-dimensional consolidation test and the triaxial permeability test was 1.20 and 1.21 at the age of 28d and 60d, respectively, and the coefficients of variation were 0.24 and 0.17, respectively. (2) When the water-cement ratio is between 5.88 and 3.85 and the water-bentonite ratio is between 7.14 and 3.85, the permeability coefficient decreases significantly with the increase of age. The ratio of the permeability coefficients at 60d and 28d in age is not significant depending on the test method. (3) When the water-cement ratio and water-bentonite ratio in the mud are certain, the silty clay is blended, and the water-soil ratio decreases from 50 to 10, and the permeability coefficient decreases linearly.